2001
DOI: 10.1034/j.1600-065x.2001.1820108.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ regulatory cells in acquired MHC tolerance

Abstract: Tolerance to self-antigens is an ongoing process that begins centrally during T-cell maturation in the thymus and continues throughout the cell's life in the periphery by a network of regulated restraints. Remaining self-reactive T-cells that escape intrathymic deletion may be silenced within the peripheral immune system by specialized regulatory CD4+ cells. By analogy, regulatory CD4+ cells that control immunity to "acquired self" should arise in circumstances where the immune system acquires tolerance to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…Experimental transplantation of high doses of allogeneic cells results in tolerance, [13][14][15][16][17][18][19][20][21] and there are reports that this effect may be mediated by regulatory T cells (T regs ). 62 Recent studies using a NIMA mouse model have demonstrated that mice that accepted allogeneic heart grafts exhibit donor microchimerism, 23 and possess higher frequencies of T regs and TGF-␤ ϩ IL-10 ϩ CD4 ϩ cells than mice that rejected their allografts. 23,24 However, tolerance to NIMA-bearing heart allografts was observed only when the mice were exposed to NIMA both in utero and after birth via breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental transplantation of high doses of allogeneic cells results in tolerance, [13][14][15][16][17][18][19][20][21] and there are reports that this effect may be mediated by regulatory T cells (T regs ). 62 Recent studies using a NIMA mouse model have demonstrated that mice that accepted allogeneic heart grafts exhibit donor microchimerism, 23 and possess higher frequencies of T regs and TGF-␤ ϩ IL-10 ϩ CD4 ϩ cells than mice that rejected their allografts. 23,24 However, tolerance to NIMA-bearing heart allografts was observed only when the mice were exposed to NIMA both in utero and after birth via breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates a marked trend toward increased gene expression of the immunosuppressive cytokine TGF-␤ after FC transplantation (P ϭ .2; Student t test.). Given the importance of TGF-␤ in inducing immunoregulatory tolerance, 26,27 the trend toward increased TGF-␤ gene expression in HSCϩFC recipients suggested that the FC is a regulatory T cell or that regulatory T cells are induced after FC transplantation.…”
Section: Fc Recipients Characterized By Increased Gene Expression Of mentioning
confidence: 99%
“…1,2,[16][17][18][19] These results demonstrate that the immune system from healthy animals contains natural regulatory CD4 T cells that actively suppress autoreactivity. In animal models, several studies have shown that regulatory CD4 T cells, besides their pivotal role in maintaining self-tolerance, also regulate homeostasis of the peripheral T-cell pool, 20 contribute to tolerance induction after solid organ transplantation, 21,22 and promote tolerance to allogeneic bone marrow grafts. 23,24 These findings have opened new prospects for immunotherapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%